Fertigation of Arundo donax L. with different nitrogen rates for biomass production. (February 2020) - Cano-Ruiz, J.; Sanz, M.; Curt, M.D.; Plaza, A.; Lobo, M.C.; Mauri, P.V.
Abstract: Arundo donax L. has been recognized as a promising biomass crop for bioenergy and biobased applications. Previous nitrogen fertilization studies of this crop were based on conventional fertilizer application (broadcast). Fertigation is considered an efficient strategy to reduce nutrient loss in irrigated crops. The objective of this study was to investigate the effect of nitrogen fertigation on A.donax grown in low fertility soil, under a continental Mediterranean climate. Three levels of nitrogen supply (N) were studied: 0 N (0 kg ha −1 year −1 ), 60 N (60 kg ha −1 year −1 ); and 120 N (120 kg ha −1 year −1 ). Biometric parameters, leaf chlorophyll content, leaf weight percentage, biomass production and biomass quality as well as soil macronutrient concentration were evaluated. Nitrogen use efficiency and energy yield increase due to fertilization were also determined. Compared with unfertilized plants, fertigation increased plant height, basal diameter of stem, chlorophyll content, biomass production and fiber composition. However, the increase in N rate from 60 to 120 kg ha −1 year −1 did not affect biomass yield. Energy increase due to N fertigation and nitrogen use efficiency led to the recommendation of using a fertigation N rate of 60 kg ha −1 for the A.donax cultivation in these experimental conditions. Highlights: Fertigation is an efficient strategy for fertilization of irrigated energy crops. Fertigation technique has been investigated in a crop of Arundo donax . Nitrogen applied by fertigation affects positively Arundo donax biomass production. The lowest dose (60 kg ha −1 N) showed better results in energy increase and NUE.